A mixed methods evaluation of a third wave cognitive behavioural therapy and osteopathic treatment programme for chronic pain in primary care (OsteoMAP). (June 2017) - Carnes, D.; Mars, T.; Plunkett, A.; Nanke, L.; Abbey, H.
Abstract: Introduction: The aim of this study was to evaluate the implementation of a 'third wave' cognitive behavioural therapy and osteopathic treatment programme (OsteoMAP) and explore its effect on patients with chronic musculoskeletal pain. Method: This evaluation included a non-randomised before-and-after patient reported outcomes study with an embedded fidelity evaluation. Patients were seen for 1 h per week for six weeks. They received a questionnaire prior to receiving treatment and six months later. A purposive sample of patients were interviewed and clinical sessions were observed to evaluate competence and adherence to the intervention manual. Results: 208 patients were enrolled and 86% attended 3 or more OsteoMAP sessions. 82 students were trained to deliver the intervention under supervision. They were >90% adherent to the manual in 8 of the 12 domains measured. At baseline (n = 147), 69% of patients were female, 64% white and 77% reported pain for more than one year. At 6 months (matched pairs n = 63), there were clinically important changes of 58% in a composite score for pain, function, mood and coping (Bournemouth Questionnaire) and significantly higher psychological flexibility scores (difference in means 6.98 (95% CI 4.2, 9.8)) (Acceptance and Action Questionnaire). No statistically significant change was seen in mindfulness (Freiburg Mindfulness Inventory), 30% of patients reported temporary symptom increases during the course but 95% were satisfied or very satisfied with their overall experience and outcomes. Conclusions: OsteoMAP was feasible, well received with some beneficial effects. Integrating psychological and osteopathic care shows promise and further research is warranted to assess effectiveness.